Cartografia e Quilombos: Territórios étnicos africanos no Brasil - Anjos, Rafael Sanzio Araújo dos (Africana Studia, 2020)
This work aims at contributing with geographical information in the construction of a new profile of the African cultures and of the Brazilian black people in the formation of the country; which still lacks investigation and knowledge. In Brazil, the remains of quilombo, “mocambo”, “comunidades negras rurais”(rural black communities) or “terras de preto” (nigger´s lanas) are part of the same immeasurable cultural patrimony, most of which is still unknown to the State, to the authorities and to the official land control and territorial policies. The study pointed out that the topic of quilombos remains in Brazil cannot be treated with punctual actions nor be involved by conflicts of institutional attributions. The achievements in this matter do not reflect a plan of action which clear premises and parameters of short and medium terms, clarifying mainly the number of sites that will be benefited by this, for how long and what resources will be used. The data bank of registration of quilombos communities remains reveled 1300 occurrences. This spatial fact shows the importance of the Northeast and the North regions of the country to the understanding of the expansion and concentration of the quilombos remains; as well as it reassures the relevance the these states in the rescue of the identity and in the construction of a memory related to the Afro-Brazilian culture.